Selective Targeting of IL-15Rα Is Sufficient to Reduce Inflammation - Meghnem, Dihia; Maillasson, Mike; Barbieux, Isabelle; Morisseau, Sébastien; Keita, Dalloba; Jacques, Yannick; Quéméner, Agnès; Mortier, Erwan (Frontiers in Immunology, 2022)
Cytokines are crucial molecules for maintaining the proper functioning of the immune system. Nevertheless, a dysregulation of cytokine expression could be involved in the pathogenesis of autoimmune diseases. Interleukin (IL)-15 is a key factor for NK and CD8 T cells homeostasis, necessary to fight cancer and infections, but could also be considered as a pro-inflammatory cytokine involved in autoimmune inflammatory disease, including rheumatoid arthritis, psoriasis, along with TNF-, IL-6 and IL-1. The molecular mechanisms by which IL-15 exerts its inflammatory function in these diseases are still unclear. In this study, we generated an IL-15-derived molecule called NANTIL-15 (New ANTagonist of IL-15), designed to selectively inhibit the action of IL-15 through the high affinity trimeric IL-15R/IL-2R/c receptor while leaving IL-15 signaling through the dimeric IL-2R/c receptor unaffected. Administrating of NANTIL-15 in healthy mice did not affect the IL-15-dependent cell populations such as NK and CD8 T cells. In contrast, we found that NANTIL-15 efficiently reduced signs of inflammation in a collagen-induced arthritis model. These observations demonstrate that the inflammatory properties of IL-15 are linked to its action through the trimeric IL-15R/IL-2R/c receptor, highlighting the interest of selectively targeting this receptor.